Spatial distribution, prevalence and epidemiological risk factors of cysticercosis in cattle from state of São Paulo, Brazil, slaughtered for human consumption - Rossi, Gabriel Augusto Marques [UNESP]; Lopes, Welber Daniel Zanetti; de Souza Almeida, Henrique Meiroz [UNESP]; Soares, Vando Edésio; Aguilar, Carlos Eduardo Gamero [UNESP]; Vidal, Ana Maria Centola; Prata, Luiz Francisco [UNESP]; Ferraudo, Antonio Sergio [UNESP] (Elsevier, 2017)
This present research focused on establishing the prevalence, geospatial distribution and epidemiological risk factors for bovine cysticercosis in the state of São Paulo, Brazil, in cattle slaughtered for human comsumption. Data about the inspection of 104,180 bovine carcasses from 215 farms and from 70 municipalities were gathered between January and December of 2012. A cluster analysis was performed in order to correlate some variables: prevalence of bovine cysticercosis, total coffee harvesting area (hectares), orange producing areas (hectares) and Human Development Index. Afterwards, distribution maps were created in order to help the results interpretation. An average prevalence of 2.9% was established in the state of São Paulo during the studied period. The Administrative regions of São José do Rio Preto and Campinas had higher risk for cysticercosis (OR1 and 95% CI 1). The cluster analysis showed a grouping (G1 cluster) of the variables: prevalence of bovine cysticercosis, total area of sugar cane harvested, total area of orange harvested and total area of coffee harvested. This agrroupment allows us to infer that cyticercosis cases in this region are correlated with those variables distribution. Such aspects indicate that the presence of temporary rural workers and other socioeconomic and cultural features in each region can contribute to bovine cysticercosis dissemination in some areas.
Keywords: Cysticercus bovis; Spatial analysis; Taenia saginata; Zoonoses